Correlation between balance and the level of functional independence among elderly people - Prata, Melina Galetti; Scheicher, Marcos Eduardo (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: As the overall number of elderly people increases there is a corresponding rise in the number of older persons with disabilities. In order to examine whether there is any relationship between balance and activities of daily living, we evaluated balance and daily activities among elderly people living in the community. DESIGN AND SETTING: Cross-sectional study at Universidade Estadual Paulista (Unesp), Marília, São Paulo, Brazil. METHODS: The study included 70 community-dwelling elderly people aged 65 and over. Balance was evaluated using the Berg Balance Scale (BBS) and physical independence in daily activities was evaluated using the Barthel Index (BI). The Spearman correlation coefficient was used to examine the relationship between the parameters evaluated. Significance was set at the level of 5% (P < 0.05). RESULTS: The population’s mean age was 70.5 ± 5 years. The mean BBS score was 50.9 ± 4.1, whereas the mean BI score was 98.1 ± 2.8. Statistically significant relationships were found between the BBS and BI (r = 0.41; P = 0.0004); between age and BI (r = -0.24; P = 0.04); and between age and BBS (r = -0.57; P = 0.0001). CONCLUSIONS: The results showed that among elderly people, there are correlations between age, balance and independence level.